2021
DOI: 10.5187/jast.2021.e71
|View full text |Cite
|
Sign up to set email alerts
|

A retroviral insertion in the tyrosinase (TYR) gene is associated with the recessive white plumage color in the Yeonsan Ogye chicken

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…TYR encodes tyrosinase, the rate-limiting enzyme in melanin synthesis ( Sturm, 2009 ; Yang et al., 2019 ; Seruggia et al., 2021 ; Varghese et al, 2021 ). A retroviral insertion into the fourth intron of the TYR gene in chickens leads to impaired tyrosinase expression and the production of recessive white feathers ( Chang et al., 2006 ; Cho et al., 2021 ). One significant SNP (Chr1:188181166 G>C) located in the first exon of RAB38 , which is a missense mutation.…”
Section: Resultsmentioning
confidence: 99%
“…TYR encodes tyrosinase, the rate-limiting enzyme in melanin synthesis ( Sturm, 2009 ; Yang et al., 2019 ; Seruggia et al., 2021 ; Varghese et al, 2021 ). A retroviral insertion into the fourth intron of the TYR gene in chickens leads to impaired tyrosinase expression and the production of recessive white feathers ( Chang et al., 2006 ; Cho et al., 2021 ). One significant SNP (Chr1:188181166 G>C) located in the first exon of RAB38 , which is a missense mutation.…”
Section: Resultsmentioning
confidence: 99%
“…TYR is the rate-limiting enzyme and key enzyme for melanin synthesis ( Bajpai et al, 2023 ). Cho et al (2021) conducted molecular analysis of TYR and found that abnormal transcription of TYR leads to the recessive white feather phenotype. The differential expression of key genes suggests that they may be the underlying reasons for feather color differentiation in Lueyang black-bone chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the plumage and skin color of chickens may be caused by the differential expression of the TYR gene. The retroviral insertion of the tyrosinase gene ( TYR ) has been associated with recessive white mutations in chickens [ 31 ]. Nam et al [ 32 ] found, in a study on Korean native chickens, that specific mutations in the TYR gene can have important effects on melanosis in Korean native chickens.…”
Section: Discussionmentioning
confidence: 99%